Enforcement of murabahah, mudharabah, and qardhulhasan contracts in the syari'ah system - Setiawan Setiawan (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
This study examines the implementation of murabahah, mudharabah, and qardhulhasan contracts in the Syari'ah System at KSPPS Baitul Maal Wat-Tamwil